Evaluation of Lipid Profile Alterations for Early Diagnosis and Therapeutic Management of Cardiovascular and Metabolic Disorders - Arshia Mehmood, Sehrish Hafeez, Shafi Muhammad Wassan, Salma Kadir, Shamim Akram, Talmeez Zeb Shah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cardiovascular and metabolic disorders are strongly influenced by dyslipidemia, but traditional lipid markers may not fully capture cardiovascular risk. Emerging biomarkers such as non-HDL cholesterol, Apolipoprotein B (ApoB), and lipoprotein(a) [Lp(a)] offer improved risk stratification. This study evaluates lipid profile alterations and assesses the efficacy of lipid-lowering therapies. Objectives: To compare lipid profile alterations between patients with cardiovascular and metabolic disorders and healthy controls, and to assess the effectiveness of lipid-lowering therapies. Methods: A cross-sectional study was conducted on 100 participants (50 patients, 50 controls). Lipid assessments included LDL-C, HDL-C, triglycerides, non-HDL-C, ApoB, Lp(a), and oxidized LDL (OxLDL). The effectiveness of statins, PCSK9 inhibitors, and omega-3 fatty acids was analyzed. Statistical significance was set at p < 0.05. Results: Patients had significantly higher LDL-C (143.7 vs 102.4 mg/dL, p < 0.001), non-HDL-C (162.1 vs 120.3 mg/dL, p < 0.001), triglycerides (187.4 vs 104.3 mg/dL, p < 0.001), and OxLDL (2.1 vs 1.4 µmol/L, p < 0.001), while HDL-C levels were lower (37.6 vs 52.1 mg/dL, p < 0.001). PCSK9 inhibitors reduced LDL-C by 55.3% (p < 0.001), while omega-3 fatty acids lowered triglycerides by 27.1% (p < 0.001). Conclusion: Nontraditional lipid markers should be incorporated into cardiovascular risk assessment. PCSK9 inhibitors demonstrated superior LDL-C reduction, and omega-3 fatty acids effectively reduced triglycerides. Further research is needed to develop personalized lipid-lowering strategies for improved cardiovascular risk management. Keywords: Dyslipidemia, Lipid profile, Cardiovascular risk, LDL cholesterol,non-HDL cholesterol, Apolipoprotein B, Lipoprotein(a), PCSK9 inhibitors, Omega-3 fatty acids, Metabolic syndrome.